STATISTIC METHODS OF TOURIST INFORMATION SYSTEMATIZATION - A. O. Ovcharov (Russian Journal of Economics and Law)
Objective: development of statistical methods to systematize information in tourist sphere. Methods: statistical monitoring, data summarizing and grouping. Results: basing on official statistics, the necessity of tourist information systematization is proved. The features of the application of data summarizing and grouping in tourism statistics are described. For three kinds of statistical groupings, examples of official statistical reporting Rosstat are given, which prove their value in the case studies of the tourist industry. It is shown that in statistical practice the universal groups are used, combining different methods of data systematization. Scientific novelty: for the first time the opportunities are defined for statistical groupings to identify types, structures and relationships of objects, processes and phenomena in tourist sphere. The new term "statistical reductionism" is introduced, characterizing the problem of summarizing the whole statistical methodology to formal models designing. Practical value: opportunities for a broad use of data summarizing and grouping method to study the trends in the tourist industry development.